2016
DOI: 10.1091/mbc.e15-10-0747
|View full text |Cite
|
Sign up to set email alerts
|

High rates of chromosome missegregation suppress tumor progression but do not inhibit tumor initiation

Abstract: Expression of a truncated allele of the Apc tumor suppressor causes intestinal tumors with a low rate of chromosomal instability (CIN). Increasing the rate of CIN suppresses tumor growth without inhibiting tumor initiation in both the small intestine and colon, suggesting that increasing CIN is a useful chemotherapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 83 publications
1
46
0
Order By: Relevance
“…An alternative strategy is, instead, to increase the severity of CIN beyond the threshold level, so that cells become lethal. This approach must be technically feasible considering that cancer cells with CIN must have defective function in controlling mitosis [173]. Identification of the molecular basis of such a threshold point should allow the development of molecular targets (Figure 3).…”
Section: Potential Molecular Targetsmentioning
confidence: 99%
“…An alternative strategy is, instead, to increase the severity of CIN beyond the threshold level, so that cells become lethal. This approach must be technically feasible considering that cancer cells with CIN must have defective function in controlling mitosis [173]. Identification of the molecular basis of such a threshold point should allow the development of molecular targets (Figure 3).…”
Section: Potential Molecular Targetsmentioning
confidence: 99%
“…In a landmark study, increased CIN associated with reduced CENP-E expression in CENP-E +/− mice was found to promote tumor development in lymphocytes and lungs, where aneuploidy is inherently low, but inhibited tumor growth in the liver, which has inherently higher levels of aneuploidy (Weaver et al 2007). More recently, it has been demonstrated that the increased rate of chromosome mis-segregation in compound mutant Apc Min/+ CENP-E +/− mice is associated with greater cell death and suppression of tumor progression compared to singly mutant Apc Min/+ and CENP-E +/− mice (Zasadil et al 2016). These observations collectively suggest elevating CIN as a potential chemotherapeutic strategy in a genetically sensitized background.…”
Section: Clinical Significancementioning
confidence: 96%
“…In vitro and in vivo observations from several studies have demonstrated that low levels of CIN may promote tumor initiation but at elevated levels, CIN may actually be protective and inhibit tumorigenesis (Rao et al 2005, 24:9 Weaver et al 2007, Silk et al 2013, Zasadil et al 2016. It was noticed in an earlier investigation that BubR1 +/− Apc Min/+ compound mutant mice, which exhibited increased karyotypic instability, were found to have increased formation of colonic polyps but at the same time, a notable decrease in small intestine adenomas (Rao et al 2005).…”
Section: Clinical Significancementioning
confidence: 99%
“…[16,32,72,95,96] These inconsistent findings may be explained by different rates and types of CIN in the various models. Indeed, it has been suggested that high rates of CIN inhibit tumor progression, while lower CIN rates allow for tumor evolution [5,93,94] (also see Figure 2b and c). Importantly, CIN does not only seem to affect cancer growth, but also the ability of cancer to adapt and spread as transient CIN induction can lead to tumor recurrence.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 96%
“…On the one hand CIN itself can lead to tumorigenesis in some models, [91,92] but on the other hand, CIN has been found to act as a tumor suppressor in other models. [75,93,94] Furthermore, yet other CIN models are suggesting that CIN only enhances tumorigenesis in a tumorprone background. [16,32,72,95,96] These inconsistent findings may be explained by different rates and types of CIN in the various models.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 99%